Adolescents’ Perception of Risky Sexual Behavior: Risk Factor in Rural Area - Amrina, Yassirli; Waliyanti , Ema (Universitas Muhammadiyah Yogyakarta, 2023)
Introduction – Every adolescent will increase their libido so they are always looking for more information about sex that can cause deviations, one of which is risky sexual behavior. Risky sexual behavior can cause physical, psychological and social impacts. To prevent risky sexual behavior in adolescents, it is necessary to explore adolescent perceptions of the factors that affect risky sexual behavior. Purpose – This research aims to explore adolescent perceptions of factors that affect risky sexual behavior. Methodology/Approach – This research uses aqualitative research with a phenomenological approach. Data were collected by in-depth interviews with 9 informants with an age range of 12-15 years in the Kalirandu Hamlet determined by purposive sampling. Validity test of the data using member check, thick description, dependability, and peer debriefing. Data analysis using software open code 4.03. This research is ethically worthy with the number NO.330/EC-KEPK FKIK UMY/XII/2021. Findings – The results showed that adolescents' perceptions of factors affect risky sexual behavior were divided into two, namely internal factors and external factors. Internal factors that influence risky sexual behavior are libido, gender, motivation to get pleasure, knowledge, attitudes, mutual liking, and curiosity, while external factors are lack of attention from parents, lack of sexual education from parents, religion, culture and resources. Information. Originality/ Value/ Implication –Risky sexual behavior is a problem that can cause various negative impacts for adolescents. Therefore, it is important for adolescents to know the factors that influence risky sexual behavior so that adolescents can avoid risky sexual behavior.